2001
DOI: 10.2105/ajph.91.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer size and stage in Hispanic American women, by birthplace: 1992-1995

Abstract: A B S T R A C TObjectives. This study examined whether Hispanic women with breast cancer have tumor characteristics associated with delayed detection and whether these characteristics vary by birthplace.Methods. Surveillance, Epidemiology, and End Results program data were used in examining breast cancer size and stage by racial/ethnic group and birthplace.Results. Hispanic Americans are one of the fastest growing racial/ethnic groups in the country, constituting 9% of the total US population. [1][2][3] By the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Both guidelines apply to all women in the U.S. regardless of factors that may indicate differential screening schedules. Consistent with past research (e.g., Clarke et al, 2012;Hedeen & White, 2001), in a recent comparative study researchers found that 3 in 10 Latina women were under 50 years old when diagnosed with breast cancer (Nahleh et al, 2018). Even more concerning is the fact that 8% of the women were diagnosed before the age of 40.…”
Section: Breast Cancer and Latinas: An Overviewsupporting
confidence: 76%
“…Both guidelines apply to all women in the U.S. regardless of factors that may indicate differential screening schedules. Consistent with past research (e.g., Clarke et al, 2012;Hedeen & White, 2001), in a recent comparative study researchers found that 3 in 10 Latina women were under 50 years old when diagnosed with breast cancer (Nahleh et al, 2018). Even more concerning is the fact that 8% of the women were diagnosed before the age of 40.…”
Section: Breast Cancer and Latinas: An Overviewsupporting
confidence: 76%
“…Our imputation of nativity, although an improvement over prior methods [ 49 ], is subject to some error; however, given similar sensitivity and positive predictive value rates in the method, it is likely that misclassification as foreign-born balanced misclassification as US-born. The impact on case counts within groups defined by nativity is likely small, given that nativity was imputed for about one-quarter of cancer patients, and that prior research has found high accuracy for cancer registry birthplace data [ 23 , 24 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that after all mandates are implemented, about a quarter of the uninsured population will be undocumented foreign-born residents which make up nearly half of the noncitizen foreign-born population [17, 18]. The foreign born that are diagnosed with cancer are often diagnosed at later stages which puts a greater financial burden on the health care system and reduces life expectancy [19, 20]. …”
Section: Introductionmentioning
confidence: 99%